Pemulihan Kekuasaan Kelas Dominan dan Politik Neoliberalisme - Hiariej, Eric (Global: Jurnal Politik Internasional, 2007)
In the last three decades we witness the rise of global capitalism that dominates the world. It has been quite successful in persuading governments around the globe to adopt and pursue its values, norms and policies. Departing from the view based on reason and moral superiority of capitalism that is responsible for the so called its historical victory, this article argues that the main factor is simply the politics. The rise of the dom inating global capitalism should be better understood as being closely connected to three political process that reshape the balance of class power: First, the restoration of the dominant class power at the expense of the working class, the peasants and the poor in general; second, the politics of justification for this resurgence by using neo-liberalism as ideological propaganda; and, third, the manipulation of critics to empower the very system, that is, capitalism, being criticized. The worst part of this is that the global capitalism, with its three political processes, touches upon all continents and countries, including Indonesia.